Transformative multilevel mixed methods design: A worked example for researching and advocating for the bereaved at work - Leesa Taylor; Roslyn Cameron (Methods in Psychology)
The purpose of this paper is to present a transformative mixed methods research design. This design advances the use of transformative paradigms and multilevel empirical research in mixed methods research. This design incorporates a set of key features. Firstly, it enacts the transformative worldview approach and its strong alignment to social justice, human rights and inclusivity of marginalized groups. Secondly, the design embeds quality criteria for a transformative methodology. This creates a transposing effect from the transformative paradigm to the methodology. This is also referred to as one of the dimensions of integration coherence, which means a consistent philosophical stance underpins the entire study. Thirdly, the design combines this with the stages for designing a multilevel mixed methods research design (ML-MMRD). These three key features combine to create an innovative design that is then demonstrated through the presentation of the worked example of a study which has adopted this design. The worked example draws upon two critical theories – thanatology and organizational support theory - to examine the organizational support required for bereaved employees and to expose the multifaceted impacts and vulnerabilities caused by bereavement for employees in the workplace. Additionally, the example also applies the new and more advanced mixed methods research notation system, the tailored approach to data integration and interpretation, and demonstrates advances in addressing the dynamic interdependence of the dimensions of integration in mixed methods research designs.